posted by .

midpoint of L. 1/3XY = 3.
What is the midpiont of XY?

  • Geometry -

    1/3XY = 3,
    Multiply both sides by 3:
    xy = 9,
    Mid-point = 9/2 = 4.5

  • Geometry -

    If triangle ÄXYZ is equilateral and the length of one side is 7.5, what is the perimeter of ÄXYZ and what is the measure of each angle?

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. geometry

    Whats the midpiont formula? I am totally blanking and i need it asap
  2. NewGeometry

    Line segment XY has a midpoint of L. 1/3XY = 3. What is the midpoint of XY?
  3. geometry

    Line segment XY has a midpoint of L. 1/3XY = 3. What is the midpoint of XY?
  4. geometry

    in triangle GHJ, K(2,3) is the midpoint of GH, L(4,1) is the midpoint of HJ, M(6,2) is the midpoint of GJ. Find the coordinates of G, H, and J.
  5. geometry

    In triangle DEF, A(2,3) is the midpoint of DE, B(4,1) is the midpoint of EF, and C(6,2) is the midpoint of DF. What are the coordinates of D, E, and F?
  6. Derive

    Find the derivative of sin(2x + 3y)= 3xy + 5y-2. I have this so far 1) cos(2x+3y) * d/dx (2x+3y)= 3xy' + 3y + 5y' 2) cos (2x+3y) * [2 + 3y']= 3xy' + 3y + 5y' 3) 3y' cos (2x+3y) + 2cos(2x+3y)= 3xy' + 3y + 5y' 4) 3xy' + 5y' - (3y(cos(3x+3y)= …
  7. Math (Geometry)

    Square ABCD has M as the midpoint of AB, N as the midpoint of BC, P as the midpoint of CD and Q as the midpoint of MP. If [AMNPDQ]=20, what is the value of [ABCD]?
  8. Geometry; Check answers?

    For each graph, find (a)AB to the nearest tenth and (b)the coordinates of the midpoint of AB. 1. Coordinates are A(-9, -6) B(6,6) D=19.2 Midpoint=(1.5,-6) 2.A(-2,-2) B(8,-6) D=10.77 midpoint= (3,-4) 3. A(0,3) B(-2,-2) D=5.4 Midpoint= …
  9. Geometry

    Did I solve the following correctly? I had to the fin the midpoint. A (-3, 2) B (5, -4) I did the midpoint formula: M(-3+5/2, 2+ -4/2=M (2/2, -2/2). Is (2/2, -2/2) the correct midpoint?
  10. Simultaneous equation

    X+y+z=1......(1) x^2+y^2+z^2=35........(2) x^3+y^3+z^3=97.........(3) solution but from 3 (x^3+y^3)=(x+y)^3-3xy(x+y)......(4) puting 4 into 3 bck (x+y)^3-3xy(x+y)+z^3=97.......(5) now from 1 x+y=1-z......(6) putin 6 into 7 we have …

More Similar Questions